A review of caesarean section rates in India: causes for increased prevalence and suggestions for a rational approach - Balla, Patricia Christina; Nallapu, Samson Sanjeeva Rao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
An increasing Caesarian Section (CS) rate places a clinical and economic burden on health care services of the country. When balancing an optimal CS rate, maternal and pediatric outcomes of pregnancy such as maternal morbidity and birth complications should be considered. A CS can be a life-saving intervention when medically indicated, but this procedure can also lead to short-term and long-term health effects for women and children. For society, a caesarean section is more costly than a vaginal delivery. The increased rate of CS can be attributed to medical and non-medical factors like increases in maternal age and body mass index as well as changes in obstetric practice and technology. The WHO has recommended the Robson 10 Group classification as a global standard tool for monitoring CS. This system classifies CS into 10 mutually exclusive groups based on the parity, gestational age at admission, onset of labour, fetal presentation and number of fetuses. The WHO also emphasises that the focus should be to provide caesarean sections to all women in need rather than striving to achieve any specific rate at the population level. It also encourages a shift in the focus from optimal caesarean section rates to more practical proposals which are amenable to action. In the private healthcare setup, commitment to improvement and strategies such as full time availability of obstetricians, better midwife support and regular audits will help move towards an acceptable CS rate. In conclusion, the onus must not be on just reducing CS rates but on scientific methods of deciding when a woman needs the surgery and to ensure safe healthcare environments for the same. Training in obstetrics for specialists must not neglect appropriate procedures like instrumentation.